1995
DOI: 10.1083/jcb.129.4.999
|View full text |Cite
|
Sign up to set email alerts
|

Expression and compartmentalization of caveolin in adipose cells: coordinate regulation with and structural segregation from GLUT4.

Abstract: Abstract. Native rat adipocytes and the mouse adipocyte cell line, 3T3-L1, possess transport vesicles of apparently uniform composition and size which translocate the tissue-specific glucose transporter isoform, GLUT4, from an intracellular pool to the cell surface in an insulin-sensitive fashion. Caveolin, the presumed structural protein of caveolae, has also been proposed to function in vesicular transport. Thus, we studied the expression and subcellular distribution of caveolin in adipocytes. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 57 publications
3
62
1
2
Order By: Relevance
“…Biochemical isolation and immunogold electron microscopy of plasma membranes revealed the transient localization of Glut4 immunoreactivity in lipid rafts after insulin stimulation of 3T3L1 adipocytes (Scherer et al, 1994;Gustavsson et al, 1996;Karlsson et al, 2002), although others found no evidence for Glut4 in lipid rafts (Voldstedlund et al, 1993;Kandror et al, 1995). Although this discrepancy might be the result of different methodologies, it seems possible that Glut4 initially docks and fuses at lipid rafts, due to the assembly of the exocyst in this microdomain, and then transits into nonraft domains.…”
Section: Discussionmentioning
confidence: 69%
“…Biochemical isolation and immunogold electron microscopy of plasma membranes revealed the transient localization of Glut4 immunoreactivity in lipid rafts after insulin stimulation of 3T3L1 adipocytes (Scherer et al, 1994;Gustavsson et al, 1996;Karlsson et al, 2002), although others found no evidence for Glut4 in lipid rafts (Voldstedlund et al, 1993;Kandror et al, 1995). Although this discrepancy might be the result of different methodologies, it seems possible that Glut4 initially docks and fuses at lipid rafts, due to the assembly of the exocyst in this microdomain, and then transits into nonraft domains.…”
Section: Discussionmentioning
confidence: 69%
“…This was performed on differentiated 3T3-L1 adipocytes (Kandror et al, 1995) essentially as described for rat adipocytes (Simpson et al, 1983). Cells were treated with insulin (100 nM) or carrier for 15 min at 37°C.…”
Section: Subcellular Fractionation Of Adipocytesmentioning
confidence: 99%
“…Fat cells contain a distinct population of vesicles that translocate the glucose transporter GLUT4 to the surface upon stimulation with insulin [11,12]. These vesicles are distinguished from caveolae by the absence of caveolin [13], and furthermore GLUT4 is not associated with caveolae in the plasma membrane [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that caveolae may play a role in the translocation of GLUT4-containing vesicles to the plasma membrane, either by physically mediating the vesicular contact with the plasma membrane by generating areas rich in cholesterol [13] or by regulation of exocytosis via interaction with the molecular machinery of exocytosis [2]. In line with these theories, caveolae have been shown to be associated with the following docking/fusion proteins: vesicle-associated membrane protein (VAMP), N-ethylmaleimide sensitive factor (NSF), and soluble NSF attachment protein (SNAP) [15].…”
Section: Introductionmentioning
confidence: 99%